Foreign Investment Crises In Algeria And Its Circumstantial Challenges - Atmane Medini; Abdallah Chekka (جامعة الوادي University of Eloued, 2024)
Improving the investment climate is not only linked to physical dimensions such as infrastructure and qualified human resources, but also to other dimensions related to the level of security and legislative stability. The study aimed at the comparative analysis of competitive efficiency in attracting foreign investments to the Arab Maghreb countries, namely Algeria, Tunisia, and Morocco, relying on UNCTAD data. The study utilized two levels of analysis, descriptive and statistical, to assess common integration. It was found that foreign investments in Algeria are concentrated in the extractive sectors, accounting for 61% of the total investments. The industrial complexity index for Algeria was (-1.33), indicating the failure of investment policies to direct foreign investments towards more diversified sectors. On the other hand, Tunisia demonstrated greater capability in utilizing foreign investment inflows with an industrial complexity index of (+0.88), while Morocco exhibited lower capability compared to Tunisia due to the burden of public debt. This confirms the hypothesis that the investment climate is linked to factors related to legislative stability, as well as the level of trust associated with reducing levels of financial and administrative corruption.
Keywords: investment climate; legislative stability; foreign investments; Maghreb countries